Correlation between 25-hydroxyvitamin D and severe headache or migraine: evidence from NHANES database - Xiaolei Zhang; Jiangwen Wu; Ting Wu; Liwen Guo; Ruiping Zhang; Xin Jin (Food & Nutrition Research)
Objective: This study was formulated with the objective of elucidating the correlation between 25-hydroxyvitamin D (25(OH)D) and the occurrence of severe headache or migraine, employing a cross-sectional analytical approach. Methods: A cross-sectional survey was conducted over two cycles involving 7,661 participants, utilizing data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2001 and 2004. A weighted logistic regression method was employed to construct a relationship model between the two variables. Subgroup analysis, adjusting for confounding factors, was performed through stratified analysis to explore the association between 25(OH)D and severe headaches or migraines. Finally, a restricted cubic spline regression (RCS) was utilized to investigate the non-linear relationship between the variables. Results: A total of 7,661 participants were included in this study, with an overall prevalence of severe headaches or migraines of 1,576/7,661 (22.3%). The results from all models consistently indicated a significant negative correlation between serum 25(OH)D levels and the risk of severe headaches or migraines (P < 0.05). Stratified analysis revealed that in the female population (odds ratios [OR]: 0.995, 95% CI: 0.991–0.998, P = 0.001), never smokers (OR: 0.991, 95% CI: 0.985–0.997, P = 0.003), and non-drinkers (OR: 0.993, 95% CI: 0.987–0.999, P = 0.022), the risk of severe headaches or migraines decreased with increasing serum 25(OH)D concentrations. RCS results demonstrated a linear relationship between serum 25(OH)D levels and the risk of severe headaches or migraines. Conclusion: We discovered a negative correlation between serum 25(OH)D levels and the prevalence of severe headaches or migraines, particularly in females, non-smokers, and non-hypertensive individuals. Further clinical research is necessary to confirm these findings, establish causality, and explore potential preventive and therapeutic mechanisms for migraines.